Life expectancy without depression increases among Brazilian older adults - Flávia Cristina Drumond Andrade; Fan Wu; Maria Lúcia Lebrão; Yeda Aparecida de Oliveira Duarte (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To estimate life expectancy with and without depressive symptoms in older adults for the years 2000 and 2010. METHODS We evaluated individuals aged 60 years or older (n = 1,862 in 2000 and n = 1,280 in 2010), participants of the Saúde, Bem-Estar e Envelhecimento (SABE - Health, Wellbeing and Aging) study in in Sao Paulo, Southeastern Brazil. Depression was measured using the shorter version of the Geriatric Depression Scale (GDS-15); respondents scoring ≥ 6 were classified as having depression. Estimates of life expectancy with and without depression were obtained using the Sullivan method. RESULTS Data from 2000 indicate that 60-year-old men could expect to live, on average, 14.7 years without depression and 60-year-old women could expect to live 16.5 years without depression. By 2010, life expectancy without depression had increased to 16.7 years for men and 17.8 years for women. Expected length of life with depression differed by sex, with women expected to live more years with depression than men. CONCLUSIONS Between 2000 and 2010, life expectancy without depression in Sao Paulo increased. However, older adults in Brazil, especially older women, still face a serious burden of mental illness.